Yusuf Al-Qardhawi’s Methodological Reformulation of Hadith Thought and Its Influence on the Development of Hadith Science: An Analysis in the Book of Kaifa Nata'amal ma'a al-Sunnah al-Nabawiyyah - Zulfahmi Alwi; Rahman Rahman; Zikri Darussamin; Darusman Darusman; Ali Akbar (Sekolah Tinggi Agama Islam Taruna Surabaya, 2023)
Hadith as the second source of law in Islam, has various forms of derivation of meaning depending on the form of the method as well as the approach used. To be able to understand it in depth, a comprehensive study is needed with the use of appropriate methods and approaches so as to be able to extract the meaning that exists in a hadith text. Yusuf al-Qaradawi as a contemporary Hadith scholar also offers a new methodology in an effort to understand the Hadith so as to facilitate the preachers and researchers provide penjelasn Hadith against the text used or studied. The methodology of understanding is outlined in his book entitled Kaifa Nata'amal Ma'a al-Sunnah al-Nabawiyyah. Yusuf Al-Qardawi in the book emphasizes on understanding the Hadith as an attempt to ground the Prophet's Hadith with several methods including by combining Hadith with the Qur'an, testing the validity of a Hadith with sahih hadiths that are thematic, closer to the main and more in accordance with the wisdom of Shari'ah or the general purpose of Shari'ah. This study uses a qualitative approach with descriptive analytical methods. The object of study in this article is the book Kaifa Nata'amal Ma'a al-Sunnah al-Nabawiyyah, by Yusuf al-Qaradawi. The primary source in this article is the book of Kaifa Nata'amal Ma'a al-Sunnah al-Nabawiyyah, which was written directly by Yusuf al-Qaradawi, containing all methods and steps to understand and use Hadith in daily activities. Secondary sources in this paper are obtained from books, journals, and articles related to the writing being discussed. The results showed that the reformulation of the methodology offered by Yusuf al-Qaradawi in the book Kaifa Nata'amal Ma'a al-Sunnah Al-Nabawiyyah get the pros and cons of the readers and enthusiasts of Hadith studies. Also in another aspect, the Hadith method of thought offered by him is relevant to the current historical needs. This is because the understanding of the Hadith text must be relevant to itself, in the sense that its meaning is limited to the values it contains and is relevant to the current conditions of society whose relevance takes place on a rational understanding. The perspective of Yusuf al-Qaradawi indicates the development of Hadith studies, although in this case it gets opposition from other Hadith thinkers.